2018
DOI: 10.1007/s00607-018-0663-0
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-based vulnerability assessment of operating systems and web browsers

Abstract: Organizations face the issue of how to best allocate their security resources. Thus, they need an accurate method for assessing how many new vulnerabilities will be reported for the operating systems (OSs) and web browsers they use in a given time period. Our approach consists of clustering vulnerabilities by leveraging the text information within vulnerability records, and then simulating the mean value function of vulnerabilities by relaxing the monotonic intensity function assumption, which is prevalent amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…While a number of studies utilize vulnerability data associated with separate version of software (e.g. Windows 7) on which to apply VDMs [20], [28], there are papers that consider all versions of a software together [23], [32]. The first group expects that each version of a given software is an independent and all around characterized item, yet distinguishing the sources of reliance in vulnerability data is not a simple task.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…While a number of studies utilize vulnerability data associated with separate version of software (e.g. Windows 7) on which to apply VDMs [20], [28], there are papers that consider all versions of a software together [23], [32]. The first group expects that each version of a given software is an independent and all around characterized item, yet distinguishing the sources of reliance in vulnerability data is not a simple task.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Allodi [31] demonstrated that discovered vulnerabilities may pursue a Power-law distribution. The model utilized in this paper was applied on vulnerability data as a VDM in [32], [33]. The main assumption of this model is that the number of discovered vulnerabilities pursues a nonhomogeneous Poisson process.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies applied existing VDMs or a modified versions of them to different types of software packages, such as OSs and web servers, to simulate the vulnerability discovery rate and predict the number of vulnerabilities that may potentially be present but not yet found [14]- [17]. Other studies tried to increase the accuracy of vulnerability discovery modeling by taking the skewness of the vulnerability data into consideration [8] or using the clustering techniques [18], [19], commonly used in social media studies [20] .…”
Section: Related Workmentioning
confidence: 99%
“…The NHPP has been used for analyzing software's failure times, and prediction of the next failure time. The subject model has been shown to be effective and useful not only in software reliability assessment [2]- [11], but also in cybersecurity; the attack detection in cloud systems [12] [13], breast and skin cancer treatments' effectiveness, [14] [15] [16], respectively, finance; modeling of financial markets at the ultra-high frequency level [17], trnasportation; modeling passengers' arrivals [18] [19] [20] [21] [22], and in the formulation of a software cost model [23].…”
Section: Introductionmentioning
confidence: 99%